Ethnomathematics Exploration in the Process of Manufacturing Sidikalang Coffee Powder as a Source of Mathematics Learning - Kudadiri, Nurkeke Fitriani; Andhany, Ella (Universitas Negeri Semarang, 2024)
Mathematics plays an important role in various areas of daily life and helps develop logical, critical, and systematic thinking patterns, and problem-solving abilities. However, the mathematics learning process often experiences obstacles both from internal factors such as students' negative attitudes, low interest in learning, and weak motivation, as well as external factors such as lack of teacher focus and minimal family support. Ethnomathematics, namely mathematics integrated with local culture, has emerged as an effective method to help students understand mathematical concepts more easily and interestingly. This research was conducted on the process of making Sidikalang coffee at UD (trading business) Kopi Keke, Dairi, North Sumatra, which combines ethnomathematics with mathematics learning. Through qualitative methods with an ethnographic approach, this research identifies mathematical concepts contained in the six stages of coffee making, namely drying, pounding, roasting, grinding, packaging, and marketing. The research results show that this process includes the concepts of social arithmetic, calculation, time comparison, plane geometry, space geometry, and measurement so that it can support mathematics learning that is easy for students to understand.